Pathways to Universal Electricity Access for Rural Communities in Africa. Issue 2 (November 2020) - Bahaj, A S; Alam, M; Blunden, L S; James, P A B; Kiva, I
Abstract: This paper presents results covering the efficiency of appliances to support reduce power needs in both mini grids and upgradeable solar home systems. In addition the research has compared the efficacy of DC vs AC mini grids at different scales. In general, the results indicated that DC mini grids could compete well at sites with a smaller geographical footprint, providing efficient appliances are integrated at system implementation. At the higher 'tiers' of electrification, we also present results and experiences from the five e4D solar photovoltaics (PV) mini-grid projects in Kenya and Uganda. The work includes analysis of community engagement, electrical load characterisation, and system operation of the mini grids in rural settings. The results indicate that energy consumption varies significantly between the sites, associated with socio-economic factors, whilst all the villages' trading centres have experienced varying levels of business growth. Overall outcomes from this research provide clear indications that mini-grid interventions not only invigorate rural communities by enhancing education and health provisions, but are also associated with growth in existing businesses and the creation of new businesses. Therefore, it is recommended that where needed, rural electrification policies be amended to give priority to facilitate and attract investment in decentralized mini grids.